2012
DOI: 10.2478/v10172-012-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure of Annealed Galfan Coating on Steel Substrate

Abstract: The Microstructure of AnnealedGalfanCoating on Steel SubstrateThe commercially availableGalfancoating containing 5-7wt.% of Al deposited on the low carbon steel substrate by hot dipping has been examined with respect to the microstructure of the coating/substrate interface area. The application of several experimental techniques (SEM/EDS, XRD, TEM/AEM/EDS/ED) allowed demonstrating the two-phase structure of the alloy coating in non-treated, commercially availableGalfansamples: Zn-rich pre-eutectoidηphase grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…The presence of Fe was a result of the alloy spelter being taken from the process galvanising bath that is saturated with Fe due to the constant movement of steel strip through it. The XRD data for the sample with no ultrasound provided in figure 7 showed a crystalline structure and peak identification through comparison to previous research on this alloy enabled the identification of  Zn and  Al phases as the predominant structures in the sample [27]. The EDX and XRD data presented support previous research into similar alloys [26,27,28] that the microstructure was composed of primary Zn rich  dendrites surrounded by a eutectic of  Zn /  Al as described in section 3.…”
Section: Accepted Manuscriptsupporting
confidence: 76%
“…The presence of Fe was a result of the alloy spelter being taken from the process galvanising bath that is saturated with Fe due to the constant movement of steel strip through it. The XRD data for the sample with no ultrasound provided in figure 7 showed a crystalline structure and peak identification through comparison to previous research on this alloy enabled the identification of  Zn and  Al phases as the predominant structures in the sample [27]. The EDX and XRD data presented support previous research into similar alloys [26,27,28] that the microstructure was composed of primary Zn rich  dendrites surrounded by a eutectic of  Zn /  Al as described in section 3.…”
Section: Accepted Manuscriptsupporting
confidence: 76%
“…According to these SAD patterns, it could be concluded that the needle-like Fe-Al phase in BFI images was FeAl 3 . 30,31) The result is in accordance with the result of EPMA line analysis. Moreover, the characteristic feature of twinning with refection plane (001) along [010] axe could also be observed in Fig.…”
Section: Microstructure Of the Cladding Layerssupporting
confidence: 79%